Pulmonary Vein Isolation Using Pulsed Field Ablation With vs Without Posterior Wall Isolation in Patients With Symptomatic Persistent Atrial Fibrillation - Laurent Roten; Jens Maurhofer; Philipp Krisai; Alexander Breitenstein; Pascal Koepfli; Ardan M. Saguner; Florian Franzeck; Patrizio Pascale; Thomas Kueffer; Sven Knecht; Corinne Jufer; Valon Spahiu; et al. (JAMA, 2026)
Importance Pulmonary vein isolation (PVI) is less effective in persistent than in paroxysmal atrial fibrillation (AF). Objective To determine whether adding posterior left atrial wall isolation (PWI) to pulsed field ablation (PFA)–based PVI reduces atrial tachyarrhythmia in patients with persistent AF. Design, Setting, and Participants This investigator-initiated, multicenter, randomized superiority trial with blinded end-point adjudication was conducted at 6 centers in Switzerland. Patients with symptomatic, persistent AF were enrolled from November 2023 to February 2025, with 1-year follow-up completed February 2026. Intervention Patients were randomized 1:1 to PFA-based PVI with PWI vs PFA-based PVI alone. All patients received an implantable cardiac monitor (ICM) after ablation. Main Outcomes and Measures The primary end point was first recurrence of atrial tachyarrhythmia during days 91 to 365 after ablation, detected by continuous ICM monitoring and adjudicated by an independent clinical events committee blinded to treatment allocation. There were 29 secondary end points, including atrial arrhythmia burden during days 91 to 365, time to arrhythmia recurrence during days 91 to 365 using different minimum episode durations, and a safety composite, which comprised cardiac tamponade requiring drainage, persistent phrenic nerve palsy lasting more than 24 hours, serious vascular complications requiring intervention, stroke or transient ischemic attack, atrioesophageal fistula, or death up to day 90. Results Among 206 randomized patients (mean [SD] age, 65.8 [9.2] years; 165 [80.1%] males; 102 randomized to PVI with PWI; 104 randomized to PVI alone), atrial tachyarrhythmia recurred in 51 of 102 patients (50.6%) assigned to PVI with PWI and in 63 of 104 patients (60.6%) assigned to PVI alone (rate ratio [RR], 0.75 [95% CI, 0.51-1.09]; P = .13). Of the 29 prespecified secondary outcomes, 22 were not significantly different. The mean atrial arrhythmia burden was 6.9% and 11.0%, respectively (difference, −4.1 percentage points; 95% CI, −8.0 to −0.2 percentage points; P = .04). Across minimum episode durations of 1 hour or longer, 6 hours or longer, 1 day or longer, 2 days or longer, and 7 days or longer, RRs for PVI with PWI vs PVI alone were 0.64 (95% CI, 0.41-0.99), 0.62 (95% CI, 0.38-1.03), 0.37 (95% CI, 0.18-0.78), 0.40 (95% CI, 0.18-0.88), and 0.51 (95% CI, 0.22-1.23), respectively. The safety composite end point occurred in 2 patients assigned to PVI with PWI. Conclusions and Relevance In patients with persistent AF, adding PFA-based PWI to PVI did not significantly reduce atrial tachyarrhythmia recurrence lasting 30 seconds or longer compared with PVI alone. The findings for secondary end points are hypothesis generating and warrant further evaluation in a larger trial. Trial Registration ClinicalTrials.gov Identifier: NCT05986526